2021
DOI: 10.3390/ma14082087
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure, Mineralogical Characterization and the Metallurgical Process Reconstruction of the Zinc Calcine Relics from the Zinc Smelting Site (Qing Dynasty)

Abstract: The smelting of zinc is considered as one of the most challenging technologies in ancient civilization. Compared with non-sulfide zinc ores, the smelting of zinc sulfide ores is more complicated since they have to be roasted before smelting. The technological smelting process of the ancient zinc metallurgy technology has been studied and partly reconstructed. However, the roasting technology, including the roasting conditions and involved metallurgical processes, is still unclear. The discovery of the zinc sme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
(33 reference statements)
0
2
0
Order By: Relevance
“…When heated, zinc ore was reduced to metallic zinc vapor and diffused into copper, forming brass then. Finally, in the third stage dated back to around the fifteenth century and with the availability of zinc metal, brass could be obtained by smelting pure copper and metallic zinc [17]. Thus, the composition distribution and metallographic structure of the sample were consistent with brass prepared by smelting copper ore [35,36] consisting in melting an appropriate mixture of zinc ore and copper ore over 920 °C [12,22].…”
Section: Technical Features Of Brass In the Coronetmentioning
confidence: 91%
See 1 more Smart Citation
“…When heated, zinc ore was reduced to metallic zinc vapor and diffused into copper, forming brass then. Finally, in the third stage dated back to around the fifteenth century and with the availability of zinc metal, brass could be obtained by smelting pure copper and metallic zinc [17]. Thus, the composition distribution and metallographic structure of the sample were consistent with brass prepared by smelting copper ore [35,36] consisting in melting an appropriate mixture of zinc ore and copper ore over 920 °C [12,22].…”
Section: Technical Features Of Brass In the Coronetmentioning
confidence: 91%
“…However, based on numerous excavations, the mass manufacturing of brass products and brass coins could have occurred in China not earlier than in the fifteenth century, though According to scientists, Chinese brass technology could have become widespread during the Ming Dynasty (明) epoch [13]. Although the appearance of elemental zinc metal in China is also dated back to the Ming Dynasty period [14,15], brass could be obtained by smelting copper-zinc symbiotic ore, copper-zinc mixed ore or copper with zinc oxide ore earlier [12,16,17]. Various new studies revealed that almost certainly brass was employed much earlier.…”
Section: Introductionmentioning
confidence: 99%